Analisis Implementasi Hukum Internasional, Perubahan Iklim dalam Tata Kelola Lingkungan Indonesia - Slamet Komarudin; Satriyo Pratomo; Dwi Imroatus Sholikah (IAI Nasional Laa Roiba Bogor, 2025)
To address global issues such as climate change, countries must cooperate through the implementation of strong international law. Due to its high ecological vulnerability, Indonesia must play a significant role in global commitments to climate change mitigation and adaptation. The purpose of this study is to examine how international legal instruments, such as the Paris Agreement and the United Nations Framework Convention on Climate Change (UNFCCC), are applied in Indonesian environmental governance. This research used a juridical-normative approach, conducting a qualitative analysis of government policies, national regulations, and relevant academic literature. The study shows that Law Number 32 of 2009 concerning Environmental Protection and Management, along with its various derivative regulations, have incorporated international climate change principles into Indonesian national regulations. However, suboptimal environmental law enforcement, limited regional capacity, and poor inter-agency coordination remain challenges. To ensure the effective implementation of international law in the country, policy harmonization, institutional capacity building, and legal system strengthening are needed.